Combinar o corte de trepadeiras com o plantio de mudas de árvores é a melhor estratégia para restaurar as bordas de florestas estacionais semideciduais - Santos, Guilherme Aparecido Melo (2024)
Due to the negative impacts of overabundant climbers on the structure of tropical forests, it is necessary to restore and manage degraded fragments. Climbers become extremely abundant in degraded tropical forest fragments, creating a significant demand for ecological restoration. In these cases, the main restoration strategy has been climbing plants cutting, but it is still necessary to understand the outcomes of cutting in combination with the planting of native tree seedlings (cutting + planting), especially at the edges of fragments, which are subject to greater disturbances than the forest interior. We tested whether cutting + planting is the best strategy to restore a degraded edge of a Semideciduous Seasonal Forest fragment in southeastern Brazil. To do this, we used mixed linear models to evaluate the effect of cutting + planting, cutting, and no management (control) on the density and basal area of climbers, the density and basal area of trees, the percentage of dead trees, and the density, species richness, and diversity of seedlings 8 years after the start of the experiment. Cutting + planting resulted in the greatest decrease in climbing plants density and basal area, and the greatest increase in tree density and seedling diversity. Although cutting + planting reduced the percentage of dead trees and increased seedling richness, these variables were more affected by cutting alone. Management had no effect on the basal area of trees and the density of seedlings. This study provides evidence that cutting climbers combined with planting native tree seedlings is the best strategy to restore degraded edges of tropical seasonal forests, as it reverses the trajectory of increasing dead trees and decreasing tree density and diversity resulting from the excessive abundance of climbers.